Hubungan Kepemilikan dan Kinerja Keuangan pada Perusahaan - Cindy Radinca; Riesanti Edie Wijaya (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
This study aims to determine the effect of capital structure on firm financial performance. This research method uses a quantitative approach. The object of this research is manufacturing firm sector consumer goods industry listed on the Indonesia Stock Exchange in the period 2013-2017. The sample used in this research is 130 years- firms. The dependent variable used is firm performance as measured by Return on Asset (ROA) and Return on Equity (ROE). The independent variable used is capital structure as measured by debt ratio or debt to total asset ratio. And, the control variable used is asset turnover, age of firm, and growth opportunity. The results of this study indicate that the capital structure has a negative relationship and significant on firm performance. This result can be supported by trade-off theory and agency theory. Control variable asset turnover has a positive relationship and significant on firm performance, the age of firm has a positive relationship and significant on firm performance, and growth opportunity has a positive relationship and non-significant on firm performance